A study of faculty-librarian relationships in selected private colleges and universities in Greater Manila - Flores, Nancy D., 1949-
Although some 85 per cent of the total faculty respondents assist the librarians in developing the library collection, the extent and degree of faculty participation in the collections development program of the library leave much to be desired. Majority of the faculty respondents noted that their participation in the above-mentioned activity is only done "occasionally" as summarized in table 14. It is therefore indicated that librarians must find ways and means of securing adequate faculty participation in this vital task of the library.
It is significant to note that the survey revealed that the librarian respondents have a general tendency to indicate a much higher rating or evaluation of library services than the faculty. In other words, librarians have a marked tendency to paint a much brighter and rosier self-image of the library than what is perceived by the faculty clients.
The analysis of data likewise supported the initial contention of the writer that the degree of satisfaction in library services of the faculty is largely influenced by the quality and quantity of services provided by the library staff. This finding is clearly shown in Tables 9-13 of the integrated findings.
The survey likewise revealed a need to test and validate further the proposed library staff ratios for libraries in private higher education. Data strongly suggest that a lower librarian/clientele (students and faculty) ratio would enhance library services and achieve a higher degree of satisfaction from the clientele.
The survey showed and discovered a general degree of satisfaction and harmonious interpersonal relations between the faculty and the librarians. This finding is significant within the context of the Philippine value sytem, which according to Lynch, emphasizes the general desire for "smooth interpersonal relations" or SIR for short, in official and/or personal transactions.
This special problem was aimed at analyzing and evaluating the existing relationships between faculty and librarians in selected private colleges and universities in Greater Manila. It focused primarily on the importance of enhancing faculty-librarian relationships with the end in view of developing effective library services for the academic community.
This study also revealed that the faculty respondents take positive measures in relating the library to the teaching function of their respective institutions. However, there is a need for a closer collaboration between the faculty and the librarians in the task of library orientation.
Thesis (M.L.S)--University of the Philippines, Diliman
Typescript.
Keywords: College librarians--Philippines--Manila Metropolitan area; College teachers--librarians relationships; Libraries, University and college--Philippines--Manila Metropolitan area